TECHNO-ECONOMIC ANALYSIS AND DESIGN OF CO2 TRANSPORTATION AND STORAGE FACILITIES.CASE STUDY: SUBANG GATHERING STATION - Soritua Sianturi, Arief
The rapid increase in the concentration of anthropogenic greenhouse gases in the atmosphere is identified as a threat to sustainable development for the global economy. Carbon capture and storage (CCS) is one of the main solutions to overcome global warming and is an effort to decarbonize fossil energy which is still the backbone of world energy today. Fossil fuels such as natural gas in the production process require a separation and purification process in the form of CO2 capture to meet the commercial quality of the gas. The carbon economic value policy which started in Indonesia in early 2023 regulates an emissions trading mechanism for carbon produced from the coal-fired electricity generation process, followed by plans to implement additional mechanisms in the form of levies (taxes) on each carbon produced which will be effective from 2026 with broader targets. This research aims to explore a series of processes for capturing, conditioning, transporting and storing carbon. From a technical perspective, the process of designing a multi-stage compressor, heat exchanger, dehydration system and distribution pipe was carried out. The design and calculation process were carried out analytically with the support of using Aspen HYSYS V11 software. This is then continued with an economic study by modeling investment and operational costs to determine the Net Present Value (NPV) achievement. In general, CCS projects are economically unattractive projects because there is no added economic value generated yet, but this research will also provide alternative solutions to support the achievement of positive NPV. Based on the results of technical calculations, a multi-stage CO2 compressor with a total power of 3.87 MW, seven heat exchanger units with a total duty of 4.45 MW, a tri-ethylene glycol flow volume of 6,190 USGPD for dehydration and a 6" distribution pipe for flowing CO2 are required. to the storage point. Furthermore, from economic calculations, an NPV of -$22,512,567 is obtained for scenario I (baseline), and an NPV of -$20,338,169 for scenario II (integration with existing facilities), and to obtain an NPV ? $0 the expected carbon price is ? $56.4/tCO2e.